2021
DOI: 10.3390/brainsci12010003
|View full text |Cite
|
Sign up to set email alerts
|

From Shunt to Recovery: A Multidisciplinary Approach to Hydrocephalus Treatment in Severe Acquired Brain Injury Rehabilitation

Abstract: Background: Hydrocephalus among Severe Acquired Brain Injury (SABI) patients remains overlooked during rehabilitation. Methods: A retrospective cohort study was carried out of traumatic and non-traumatic SABI patients with hydrocephalus, consecutively admitted over 9 years in a tertiary referral specialized rehabilitation hospital. Patients were treated with ventriculoperitoneal shunt before or during inpatient rehabilitation and assessed using the Level of Cognitive Functioning Scale and Disability Rating Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…The EP rated the use of programmable valves as inappropriate for the fixed valve, reflecting the literature data available ( Ting et al, 2020 ; Gill et al, 2021 ; Zhang et al, 2022 ; Castellani et al, 2021 ). This indication is reasonably related to the possibility of hypershunting due to a modification of CSF dynamics that can occur during the postoperative follow-up or due to the presence of an overtreated ventriculomegaly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EP rated the use of programmable valves as inappropriate for the fixed valve, reflecting the literature data available ( Ting et al, 2020 ; Gill et al, 2021 ; Zhang et al, 2022 ; Castellani et al, 2021 ). This indication is reasonably related to the possibility of hypershunting due to a modification of CSF dynamics that can occur during the postoperative follow-up or due to the presence of an overtreated ventriculomegaly.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional valve has been reported as an additional option in fewer reports ( Zhang et al, 2022 ; Castellani et al, 2021 ) ( Table 2 ). A recent systematic review and meta-analysis conducted by Ahmed et al (2023) revealed that the summary of the proportions of the incidence rate of complications was less for Adjustable Differential Pressure Valves (ADPV) as compared to Fixed Differential Pressure Valves (FDVP), but the confidence intervals overlapped.…”
Section: Discussionmentioning
confidence: 99%
“…16 More quantitative approaches have used phase contrast MRI for differentiating the reportedly obstructed and functioning shunts. 17 Phase contrast is used in many quantitative techniques for flow measurements, 8,18 but there are challenging spatial resolution requirements that must be met to achieve quantitative accuracy with flow rate (velocity) measurements in the shunt. The diameters of shunt tubes are 1 ∼ 2 mm, and ideally three to four pixels must be included across the lumen of the shunt tube in both directions to achieve an accurate measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The main causes of hydrocephalus include the loss of bone flap support, the impact of atmospheric pressure outside the intracranial abnormal pressure, as well as local brain tissue in the bone window location and position shift, all of which result in varying degrees of cerebral perfusion disorders and cerebrospinal fluid circulation disorders, cerebrospinal fluid accumulation, and oppression subarachnoid and brain pool ( 7 ). Currently, cranioplasty (CP) and ventriculoperitoneal shunt are the two major treatments (VPS) ( 8 ) CP can effectively solve circulatory disorders and insufficient blood supply caused by skull defects and improve the appearance of patients, brain tissue safety and neurological function ( 9 ). VPS is the drainage of excess cerebrospinal fluid from the ventricles of the patient into the abdominal cavity and absorption, thereby improving the symptoms of hydrocephalus ( 10 ).…”
Section: Introductionmentioning
confidence: 99%